Transformasi Struktur Ekonomi dan Sektor Unggulan di Kabupaten Buleleng Periode 2008-2013 - Wiwekananda, Ida Bagus Putu; Suyana Utama, I Made (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 1, Februari 2016 (pp. 1 - 88)DO - 10.24843/JEKT.2016.v09.i01.p04)
The impact of development of a region, such as the changes in what sectors increases or decreases, the knowledge of which is important in the development of a region. High structural change and sectoral levels, are related to the process of economic growth.  This study aims to analyze the economic structure and economic growth in Buleleng. The analytical tool used is LQ along with the shift share, and DLQ. This study used secondary data obtained from the Central Statistics Agency (BPS). Results of LQ are four sectors that constitute the base sectors namely, agriculture, mining and quarrying, manufacturing, and services. Shift share analysis results of employment shows that the services sector absorbs the most labor followed by the construction sector, PHR sector, while the agricultural sector showed a decrease in employment. Shift share analysis results for the GDP contribution of the sector number shift share analysis PHR gives the largest contribution in Buleleng followed by the services sector, followed by agriculture sector.
Keywords: economic growth, structural transformation of the economy, leading sectors LQ, DLQ, Shift Share